The Singapore-Australia green economy agreement: a template for cooperation in the green economy? - Randhawa, Dipinder Singh (2023)
The Singapore-Australia Green Economy Agreement is a pioneering agreement that seeks to accelerate the transition to a net-zero emissions economy. If it gains traction, it could provide a template for other regional economies, and perhaps even at the multilateral level – to help countries deploy trade and investment policies to meet their net-zero emissions under the Paris Agreement of 2015.